Competing discourses of risk and woman-centred care: challenges for midwives and women - Divall, Bernie (Birth and Parent Education Ltd., 2018)
Pregnant women and their birth partners require detailed, evidence-based information from healthcare professionals throughout pregnancy and birth, in order to make informed decisions about their care choices and preferences. However, healthcare professionals - particularly midwives - operate within competing discourses of risk avoidance and woman-centred, personalised models of care, and bring their own perceptions of risk to the discussions they have with women. This article outlines the concept of risk and its relevance to contemporary maternity care, and using the example of birth plans, explores ways in which midwives and the women in their care might better negotiate competing discourses of risk and woman-centred care.